The love simulation [large type] - Easton, Etta (Center Point Platinum Romance (Large Print), 2025)
"Brianna Rogers has been told a time (or six) she needs to stop jumping into things head first. But when the principal rescinds his approval for a library upgrade, deciding to spend the money on a football field instead, she sees red. Literally. Brianna throws her hat in the ring and joins a team of teachers who will spend their summer in a Mars simulation. As the sister of an astronaut, this should be easy, right? What she didn't count on was the last-minute addition to the team -- Roman Major: science teacher, son of the principal, and too handsome for his own good. Roman and Brianna have been hot and cold all year, and living in close quarters intensifies their animosity and attraction. Brianna is sure he's been sent by his father to sabotage them, foiling their chance at prize money that will cover all of the school's actual needs. But each day, Roman proves himself to be a dedicated teammate and Brianna finds herself falling harder and harder. While it's clear the feeling is mutual, she can't shake the sense that he's hiding something. As the simulation nears its end, Brianna realizes she may have to make an impossible choice, between the school she's dedicated herself to, and the man who has won his way into her heart."--